Molecular phylogeny and classification of the Callerebias and other Satyrine Butterflies - Deodati, T; ALLEGRUCCI, GIULIANA; CESARONI, DONATELLA; SBORDONI, VALERIO (country:IT, 2007)
Satyrinae is the second largest Nymphalid subfamily, including a great number of species adapted to a wide array of habitats ranging from the arctic tundra to the inner corners of the tropical rain forest. However, both phylogenetic relationships and taxonomic rankings within Satyrinae are controversial and subjected to frequent changes. Our interest is focused on the Callerebias including five genera of Satyrinae inhabiting the Sino-Himalayan region (Callerebia, Argestina, Hemadara, Loxerebia, Eugrumia), whose geographical origin was still unclear. Aim of this study is to investigate phylogenetic relationships among and within these genera, by means of partial sequences of mitochondrial CO1 and 16S rRNA genes, and of EF-1α nuclear gene. The study sample included species of two putative sister taxa, namely the genus Erebia and the genus Ypthima, set against each other as representatives of Palaearctic vs. Oriental zoogeographical source. In order to draw a more general picture, the study also included species belonging to other Satyrinae genera: i.e., the Palaearctic Boeberia, Paralasa, Proterebia, Coenonympha, Synonympha, and the mainly Oriental Melanitis, Mycalesis, Penthema, Lethe, and Elymnias. Results show a well supported clade including all the Callerebias linked to Boeberia, Paralasa, Proterebia, and Erebia as well, suggesting a Palaearctic root for the Sino-Himalayan clade.